PEMANFAATAN TEKNOLOGI SISTEM INFORMASI GEOGRAFI UNTUK PEMETAAN POLA ALIRAN AIR TANAH DI KECAMATAN LIMBOTO - Aprianto Sabihi; Nurfaika Nurfaika; Syahrizal Koem (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Limboto Subdistrict, which is the capital of Gorontalo Regency, has fairly high population growth and is an area that is vulnerable to the effects of drought. This causes the availability of groundwater to decrease. This study aims to utilize the GIS application to determine the pattern of groundwater flow in the Limboto District. This groundwater flow pattern can be used as a reference for further research related to groundwater. The type of data in this study is the type of primary data. The method used in this research is a survey method, namely by measuring directly in the field. The data analysis technique used to determine the pattern of groundwater flow in Limboto Regency is utilizing software (GIS) using ArcGIS 10.7 software to obtain a map of groundwater flow patterns in Limboto District. The results of the spatial analysis of the groundwater flow pattern map in Limboto District show that water flows from the northern part of the study site to the southern part of the study site.